Changes in the Physicochemical Quality Characteristics of Cabbage Kimchi with respect to Storage Conditions. (15th January 2017) - You, Su-Yeon; Yang, Ji-Su; Kim, Sung Hyun; Hwang, In Min
Abstract : In this study, the changes in pH, organic acid content, acidity, and salinity of kimchi prepared at 0 days, stored 1–8 weeks at 4 and 10°C, and stored at room temperature for two days were analyzed. Organic acids content was analyzed by using analytical technique of high-performance liquid chromatography (HPLC). This method was also validated using quality assurance parameters of linearity, limits of detection and quantification (LOD and LOQ), precision, and spike recovery experiments. In the analysis of organic acids content (mg/kg), it was found that the kimchi stored for 1–8 weeks at 4 and 10°C showed gradual increase in the organic acids content during storage period. The order of organic acids was lactic acid > acetic acid > citric acid > malic acid > succinic acid > oxalic acid > fumaric acid. The pH values of kimchi stored at 4°C, 10°C, and 25°C were 4.1, 3.6–3.7, and 4.1, respectively.